Leksyka sportowa w wybranych felietonach "Przeglądu Sportowego" = Sports vocabulary in selected columns of the "Przegląd Sportowy" - Cieliński, Wojciech (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The main objective was the analysis of sport vocabulary characteristic of football, in the columns published in "Przegląd Sportowy". Twenty columns from "Przegląd Sportowy" were analyzed. Within the characteristic vocabulary, there are 185 people`s names and 59 sport clubs` names. The author maintains that such a great number of proper names is a feature characteristic of sport columns. Moreover, 100 vocabulary units (words and collocations) related to football were presented. Among the linguistic stylistic devices, the focus was on borrowings, abbreviations and superlative forms present in the columns.
Keywords: felieton; "Przegląd Sportowy"; nazwa własna; klub sportowy; column; proper name; sport club